STUDY ON STRENGTH BROKE (Breaking Strength) and elongation (elongation) YARN PA (Polyamide) WITH ADDITION OF SKIN STEM EXTRACT SALAM (Syzygium polyanthum) WITH DIFFERENT CONCENTRATION - fadhari, Aidil; ', Isnaniah; ', Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study will be conducted in June 2014 which was held at the Laboratory of Materials Capture Device Utilization of Water Resources of the Faculty of Fisheries and Marine Sciences, University of Riau. The method uses a completely randomized design (RAL) with the untreated control with 10 replications. Strength of PA yarn without treatment has a breaking strength of 12.1 kgf, elongation 15:35 mm, while break strength and elongation threads preserved highest of yarn treatment C with a value of 16.0 kgf breaking strength; elongation of 19.5 mm, followed by treatment B with a value of 14.5 kgf breaking strength; elongation of 17.9 mm; and treatment A with a value of 13.3 kgf breaking strength elongation of 16.6 mm. The result of a completely randomized design (ANOVA) yarn soaked with bark extract greetings with different concentrations ie 0.3 kg / liter of water 0.5 kg / liter of water and 0.7 kg / liter of water was highly significant (p <0 , 00) to the threads of control.Keywords: Concentration, End Strength , elongation